2022
DOI: 10.5935/0103-507x.20220299-en
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association of two oxygenators in parallel or in series during respiratory support using extracorporeal membrane oxygenation

Abstract: Objective To characterize the pressures, resistances, oxygenation, and decarboxylation efficacy of two oxygenators associated in series or in parallel during venous-venous extracorporeal membrane oxygenation support. Methods Using the results of a swine severe respiratory failure associated with multiple organ dysfunction venous-venous extracorporeal membrane oxygenation support model and mathematical modeling, we explored the effects on oxygenation, decarboxylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Despite these case reports, it remains unclear whether the parallel or serial connection is more effective in refractory hypoxic failure during VV-ECMO. Regarding this question, a research of the literature led to a previous study that compared parallel and serial connections of ECMO oxygenators in a porcine animal model [13]. In this study, Melro et al suggested only a minimal effect on oxygenation of either parallel or serial connection compared to a single ECMO oxygenator with the same blood flow.…”
Section: Reasons For Refractory Hypoxia Potential Mechanisms Potentia...mentioning
confidence: 96%
See 1 more Smart Citation
“…Despite these case reports, it remains unclear whether the parallel or serial connection is more effective in refractory hypoxic failure during VV-ECMO. Regarding this question, a research of the literature led to a previous study that compared parallel and serial connections of ECMO oxygenators in a porcine animal model [13]. In this study, Melro et al suggested only a minimal effect on oxygenation of either parallel or serial connection compared to a single ECMO oxygenator with the same blood flow.…”
Section: Reasons For Refractory Hypoxia Potential Mechanisms Potentia...mentioning
confidence: 96%
“…Despite these case reports, it remains unclear whether the parallel or serial tion is more effective in refractory hypoxic failure during VV-ECMO. Regarding t tion, a research of the literature led to a previous study that compared parallel a connections of ECMO oxygenators in a porcine animal model [13]. In this study, al.…”
Section: Reasons For Refractory Hypoxia Potential Mechanisms Potentia...mentioning
confidence: 98%
“…The study by Melro et al ( 6 ) has certain limitations, which have been duly acknowledged by the authors. Although their calculations are mathematically sound, they may not account for all the variables being considered, and importantly, only one type of oxygenator was used, followed by extrapolation to a two oxygenator model.…”
mentioning
confidence: 98%
“…In these extreme situations, when a patient with no lung contribution and very high cardiac output has persistent severe hypoxemia or hypercarbia, adding a second oxygenator to the extracorporeal circuit, whether in parallel or in series, might be an intuitive option. In this issue of the Revista Brasileira de Terapia Intensiva , Melro et al., ( 6 ) using a porcine model, evaluated the impact on blood oxygenation of these two circuit configurations. Additionally, decarboxylation efficacy, as well as pressure and resistance changes to the circuit imposed by the “virtual” presence of a second oxygenator, were analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation